Rancang Bangun Kapasitor Bank Otomatis Berbasis Internet Of Things (IoT) Pada Rumah Tinggal - Fahmi, Muhammad Arfan; Radwitya, Erick; Hasan, Hasan (Electrical Network Systems and Sources, 2024)
Electricity is a crucial energy source in daily life, but we often face challenges such as power losses. Factors causing power losses include resistance in distribution cables, overloads, low voltage, and other factors. To address this issue, the solution is to use capacitor banks. The use of capacitor banks can overcome these challenges by improving the power factor and reducing energy losses. Capacitor banks have proven effective in improving the power factor, but the manual operation often disrupts users. Therefore, the aim of this final project is to design and implement an automatic capacitor bank system using the Internet of Things (IoT) to enhance energy efficiency and user convenience in residential homes. This automatic capacitor bank system involves a microcontroller control unit connected with current and voltage sensors to detect the load. The IoT module allows users to monitor and control the capacitor bank remotely via a mobile application. Test results show that this system can automatically adjust the capacitor bank capacity according to power demand, improve the power factor, and significantly reduce energy consumption. The implementation of an IoT-based automatic capacitor bank in residential homes is expected to be an effective solution for improving energy efficiency and user convenience in modern home electrical systems.